Effect of NPK fertilizer on the growth and yield of eggplant (Solanum melongona) in Yellow Red Podzolic Soil - Lucky, Maylani; Tobing, Laurensius; Petronila, Kia (Contributions of Central Research Institute for Agriculture, 2024)
The eggplant plant (Solanum melongena) is a type of annual vegetable. The need for eggplant is increasing over time along with the increase in human population. SOne of the efforts needed to increase eggplant productivity is an intensification program in the form of regulating the composition of planting media and appropriate fertilization. One type of fertilizer that can be used is NPK compound fertilizer. The aim of this research is to determine the effect of NPK fertilizer on the growth and yield of eggplant plants and to find the dose that can have the best effect on the growth and yield of eggplant plants. This research was conducted on Jalan Keling Kumang, Sekadau district, West Kalimantan. This research design used a Completely Randomized Design (CRD) with one treatment factor, namely the dose of NPK fertilizer with 4 treatment levels and each treatment consisted of 5 replications. The NPK fertilizer dose treatment is, p1: 5 gram dose, p2: 10 gram dose, p3: 15 gram dose, p4: 20 gram dose. The observation variables in this research are plant height (cm), number of leaves (strands), number of fruit and fruit weight (grams). The results showed that the dose of NPK fertilizer had a significant effect on plant height and number of fruit, while the number of leaves and weight of eggplant fruit showed no significant effect.